Kajian Dampak Proses Angkutan Terhadap Segregasi Pada Campuran Aspal Panas - Alfarido, Atreyu; Putra, Sasana; Purba, Aleksander (Universitas Lampung, 2018)
One of the causes of construction failure on asphalt pavement is segregation. Which is the separation of small and large aggregate grains within a mixture, so that in a part of the coating of the pavement will be concentrated aggregate coarse and in other part will be concentrated fine aggregate. One of the factors causing segregation is the hauling distance from Asphalt Mixing Plant to the slap location. To understand this, task a study on the impact of the transport process on segregation on hot asphalt mixture from Asphalt Mixing Plant to the location of the spread. The mixture used is the Asphalt Concrete-Wearing Course type or the laston coated wear of Asphalt Mixing Plant PT. Gigging Polah Raya for work location which is 28.9 km on Jalan Sultan Agung, Bandar Lampung, Lampung and PT. Rindang Tigasatu Pratama for work location located 53.3 km on Jalan Teuku Cik Ditiro, Bandar Lampung, Lampung. Examination of sample is done trough extraction test and sieve analysis test. From the result of the research, it’s found that there is being segregation during the transport of asphalt mix mixture from Asphalt Mixing Plant to the slap location. For sample PT. Manggung Polah Raya, gradation aggregate is still within the upper and lower limits of the general specification Bina Marga 2010. As for the sample of PT. Rindang Tigasatu Pratama, the aggregate gradation is out of the upper and lower limits of the general specification of Bina Marga 2010. Factors affecting segregation are haulage distances and aggregate density. Keywords: Road Pavement, Asphalt Concrete, Segregation.